Self-assembling peptide nanofibers containing phenylalanine for the controlled release of 5-fluorouracil - Ashwanikumar N (Dove Medical Press, 2016)
Narayanan Ashwanikumar,1 Nisha Asok Kumar,2 Padma S Saneesh Babu,2 Krishnankutty C Sivakumar,3 Mithun Varghese Vadakkan,1 Parvathi Nair,1 Ilamathi Hema Saranya,1 Sivakumari Asha Nair,2 Gopalakrishnapillai S Vinod Kumar1 1Chemical Biology, Nano Drug Delivery Systems, Bio-Innovation Center, 2Cancer Research Programme, 3Distributed Information Sub-Centre (Bioinformatics Centre), Rajiv Gandhi Centre for Biotechnology, Poojappura, Thiruvananthapuram, Kerala, India Abstract: The study shows that RADA-F6 peptide with pH-responsive self-assembling nature can be effectively used as a drug delivery system for the sustained release of a potent anticancer drug 5-fluorouracil (5-FU) at basic pH. As 5-FU contains the aromatic pyrimidine ring, RADA-F6 system is suitable for entrapping an aromatic drug due to effective π–π stacking with phenylalanine and be able to show better controlled release behavior. The stability and controlled release nature of RADA-F6 in different conditions followed by 5-FU entrapment at in silico conditions was confirmed by molecular dynamics simulation taking RADA-16 as control. Cytotoxicity of the drug-loaded RADA-F6 was measured by MTT assay and cellular uptake by confocal microscopy. Physicochemical characterization and further Western blot analysis and flow cytometric studies confirm that RADA-F6 can be successfully used as an efficient vector for pH-sensitive, controlled 5-FU delivery system. Keywords: scaffold, drug delivery, nanofibrous, aromatic